2013
DOI: 10.1177/016146811311500602
|View full text |Cite
|
Sign up to set email alerts
|

ELL Policy and Mathematics Professional Development Colliding: Placing Teacher Experimentation within a Sociopolitical Context

Abstract: Background/Context A number of recent policies have specifically attacked immigrants and English Language Learners (ELLs), including Georgia's HB 87 (2011), Arizona's SB 1070 (2010), and Alabama's HB 56 (2011), among others. The policy focus of this study is Arizona's HB 2064 (2006), which added additional requirements that mandate tracking students by English language proficiency and separating English language instruction from subject matter for ELL students. Few scholars have considered how these broad soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Furthermore, Battey and his colleagues (2013) concur that teachers have mixed responses to policy changes and sometimes teachers, 'tend to adapt policies according to their students' needs and their particular classroom context' (Battey et al, 2013, p. 6). Additionally, when policy aligns to teacher beliefs, research also found that it maximizes a teacher's work (Battey et al, 2013). This seemed to resemble Evelyn's, Sadie's, and Luther's experiences in this study.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, Battey and his colleagues (2013) concur that teachers have mixed responses to policy changes and sometimes teachers, 'tend to adapt policies according to their students' needs and their particular classroom context' (Battey et al, 2013, p. 6). Additionally, when policy aligns to teacher beliefs, research also found that it maximizes a teacher's work (Battey et al, 2013). This seemed to resemble Evelyn's, Sadie's, and Luther's experiences in this study.…”
Section: Discussionsupporting
confidence: 63%
“…Teachers' beliefs about the connection between language and content was another salient finding in the literature. Battey et al, (2013) found that the majority of participants in their study believed that language and mathematics were separate entities. Other participants "conceptualized the intersection of mathematics and language as only focusing on vocabulary" (p. 30).…”
Section: The Inclusion Of Ells In General Education Classesmentioning
confidence: 93%
“…The review of the literature identified teachers' beliefs about ELLs' academic ability and potential. In their study of 44 inservice elementary school teachers, Battey et al, (2013) found that several participants equated cognitive ability with language proficiency.…”
Section: What Teachers Believe Regarding the Teaching Of Ellsmentioning
confidence: 99%
“…Professors in secondary colleges should carry out teaching training on how to teach a certain part of a subject. Kraft et al (2018) and Battey et al (2013) proposed that plenty of evidence shows that professional development programs have null effects on teacher and student outcomes. [10][11] Moreover, Liu et al (2020) suggested that a more comprehensive approach would consider a professional development program's true effect as the combination of learning and forgetting.…”
Section: Trainingmentioning
confidence: 99%